Estudio de factibilidad para la creación de un taller hidráulico en la ciudad de Guayaquil - Mera Viera, Robert Daniel (2015)
The theme done on the "Feasibility study for the creation of a hydraulic workshop in the city of Guayaquil” problems that are disclosed in the present investigation, as to Entrepreneurship and Innovation, which aims to determine theFeasibility study for the creation of a hydraulic workshop in the city of Guayaquil. The methodology used was exploratory with quantitative approach, using direct, inductive and field deductive method through market research tools such as surveys and interviews applied to Manufacturers entrepreneurs Road area Daule of Guayaquil, obtaining as results over satisfaction with the servicing of the machines by the suppliers concerned is below 50%, some of the disagreements is little or no presence of suppliers in providing service on weekends and holidays 24 hours, among others. In conclusion, we recommend hydraulic workshop in the city of Guayaquil J&R located in the streets between Machala and Jose de Antepara, focused on providing maintenance to manufacturing companies that are from 2 to 21 kilometer of road Daule…..